Dynamic Parameter Control in Simple Evolutionary Algorithms - Droste, Stefan; Jansen, Thomas; Wegener, Ingo (Universität Dortmund, 2001)
Evolutionary algorithms are general, randomized search heuristics that are influenced by many parameters. Though evolutionary algorithms are assumed to be robust,it is well-known that choosing the parameters appropriately is crucial for success and efficiency of the search. It has been shown in many experiments, that non-static parameter settings can be by far superior to static ones but theoretical verifications are hard to find. We investigate a very simple evolutionary algorithm and rigorously prove that employing dynamic parameter control can greatly speed-up optimization.
Reihe Computational Intelligence ; 89
Keywords: 004